Climate warming amplifies the frequency of fish mass mortality events across north temperate lakes. Issue 6 (23rd August 2022) - Tye, Simon P.; Siepielski, Adam M.; Bray, Andrew; Rypel, Andrew L.; Phelps, Nicholas B. D.; Fey, Samuel B.
Abstract: Recent increases of animal mass mortality events have coincided with substantial changes in global climate. Yet, tractable approaches that predict how climate change will accentuate occurrences of these ecological catastrophes remain nascent. We compiled one of the most comprehensive datasets of lentic fish mortality events, thermal tolerances of affected families, and 1.2 million air and water temperature profiles across 8891 north temperate lakes in North America. Temperature extremes within and across lakes were strongly associated with the three most frequent cause types (infectious agents, summerkills, winterkills). Thermal tolerances mediated the lethality of direct thermal stress, but mortalities of warm‐ and cold‐water fishes occurred at similar temperature deviations. Water and air temperature‐based models accurately predicted contemporary summerkills and suggested ~ 6‐ to 34‐fold increases, respectively, in their frequency by 2100. These models forecast and contextualize impending ecosystem changes in an increasingly volatile world.